The Influence of Instagram on Purchasing Decisions and Consumptive Behavior - Rochmaniah, Ainur; Puspita , Della (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
Online networks facilitate interaction, communication, messaging, information sharing, and network building among social media users. Social media is a key element in the development of the internet. This research aims to identify the influence of Instagram on purchasing decisions and consumer behavior of Alfa The research method used is associative descriptive research. Data was taken from the Co Working Space Alfa X Tenggilis customer administration in January 2024, with a population of 150 people. The sampling technique used was total sampling from the entire population. Research analysis was carried out using a simple regression linearity test. The research results show that Instagram has a positive and significant influence on purchasing decisions at Alfa attracting consumers' attention to buy more products sold by Alfa The benefit for the company is to provide information about the social media Instagram which greatly influences consumer purchasing decisions because currently consumers are more interested in buying a product online and also seeing reviews from other consumers about products on Alfax.id, a benefit for further research provide references that can be used as research references, especially in purchasing decisions and also consumer behavior.